Інтеграція обробки великих даних за допомогою нейромереж у хмарні обчислення - Сердюк, С. С. (ХНУРЕ, 2024)
The integration of cloud computing and big data processing using neural networks opens wide opportunities for the development and improvement of information analysis. This approach makes it possible to use resources efficiently, speed up data processing, and provide accurate and predictable results thanks to neural networks.
Keywords: хмарні обчислення; cloud computing